2016
DOI: 10.2196/cancer.5247
|View full text |Cite
|
Sign up to set email alerts
|

Interest in Health Behavior Intervention Delivery Modalities Among Cancer Survivors: A Cross-Sectional Study

Abstract: BackgroundEffective, broad-reaching channels are important for the delivery of health behavior interventions in order to meet the needs of the growing population of cancer survivors in the United States. New technology presents opportunities to increase the reach of health behavior change interventions and therefore their overall impact. However, evidence suggests that older adults may be slower in their adoption of these technologies than the general population. Survivors’ interest for more traditional channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 29 publications
6
28
0
Order By: Relevance
“…Interest in PA interventions has been higher among other cancer survivor populations. For example, a cross-sectional study of breast, colorectal and prostate survivors revealed about 67% were at least somewhat interested in using an exercise program to get in shape [24]. On the other hand, a large percentage (89%) of older adults believe that participating in PA would help them feel better and remain independent yet still expressed a lack of interest in PA [25].…”
Section: Discussionmentioning
confidence: 99%
“…Interest in PA interventions has been higher among other cancer survivor populations. For example, a cross-sectional study of breast, colorectal and prostate survivors revealed about 67% were at least somewhat interested in using an exercise program to get in shape [24]. On the other hand, a large percentage (89%) of older adults believe that participating in PA would help them feel better and remain independent yet still expressed a lack of interest in PA [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, gender was not predictive for intervention delivery mode. The precise role of gender differences regarding Internet access, eHealth use, and delivery mode has been ambiguous: whereas some studies found a link with gender [ 35 , 36 , 52 ], others did not find differences between males and females [ 32 , 34 , 57 , 58 ]. Additionally, it should be noted that there was only a small portion of women in this study, as a result of part of the intended target population being prostate CPS, which may have influenced the power to detect differences.…”
Section: Discussionmentioning
confidence: 99%
“…PA behavior has proven to be a predictor of delivery mode preference according to studies examining self-reported intervention modality preference. Studies in the general population and in a cancer population found that those with lower PA levels may have a preference for Web-based or computer-based interventions [ 36 , 57 ]. Others argued that those with a risk behavior (eg, low PA behavior) may prefer the instant availability and interactivity of Web-based materials [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have confirmed that looking online for health information and support has become the norm for most cancer patients: upwards of 80% [23-25]. Receiving a cancer diagnosis has become a recognized major life event, and patients and families have very high information needs in the weeks following an initial diagnosis [21,26].…”
Section: Discussionmentioning
confidence: 99%